1986
DOI: 10.1366/0003702864509268
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Alcohols, Phenols, and Carboxylic Acids Using Phosphorus-31 NMR Spectroscopy

Abstract: Derivatization of compounds containing -OH groups can be accomplished quantitatively with 1,3,2-dioxaphospholanyl chloride. The chemical shifts of phosphorus in the derivatives clearly differentiate alcohols from phenols and carboxylic acids. Quantitation is obtained by use of 31P FT-NMR spectroscopy in the presence of 2,2,6,6-tetrameth-ylpiperidinyloxy free radical to shorten relaxation times. Compounds with phosphorus chemical shifts differing by as little as 0.1 ppm can be separately determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This analytical technique was first described by Schiff et al in 1986 and then further developed and practically applied by Argyropoulos et al to study lignin and wood chemistry. , In addition to its use in lignin characterization, the above method has also been widely applied in the study of hydroxyl compounds in tannins and flavonoids, , extra-virgin olive oil, biodiesel, pyrolysis oil, hydrothermal liquefaction (HTL) biocrude, and upgraded bio-oil . The quantitative reaction between hydroxyl groups and a phosphitylating agent, such as 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane (TMDP), in the presence of a Brønsted base (Scheme ) has been employed for this purpose. , Reaction of hydroxyl groups with TMDP replaces hydroxyl protons with a nonionizable phosphorus-containing moiety (PO 2 C 6 H 12 ). As illustrated in Scheme , the phosphitylation reaction employed in this work is driven to completion in the presence of pyridine base (Pyr), which neutralizes the HCl liberated during condensation of the hydroxyl group with TMDP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analytical technique was first described by Schiff et al in 1986 and then further developed and practically applied by Argyropoulos et al to study lignin and wood chemistry. , In addition to its use in lignin characterization, the above method has also been widely applied in the study of hydroxyl compounds in tannins and flavonoids, , extra-virgin olive oil, biodiesel, pyrolysis oil, hydrothermal liquefaction (HTL) biocrude, and upgraded bio-oil . The quantitative reaction between hydroxyl groups and a phosphitylating agent, such as 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane (TMDP), in the presence of a Brønsted base (Scheme ) has been employed for this purpose. , Reaction of hydroxyl groups with TMDP replaces hydroxyl protons with a nonionizable phosphorus-containing moiety (PO 2 C 6 H 12 ). As illustrated in Scheme , the phosphitylation reaction employed in this work is driven to completion in the presence of pyridine base (Pyr), which neutralizes the HCl liberated during condensation of the hydroxyl group with TMDP.…”
Section: Introductionmentioning
confidence: 99%
“…16 Hydroxyl group types in a wide range of biomass-derived products have been effectively quantified by phosphitylation and 31 P NMR analysis. This analytical technique was first described by Schiff et al in 1986 20 and then further developed and practically applied by Argyropoulos et al to study lignin and wood chemistry. 21,22 In addition to its use in lignin characterization, 23−25 the above method has also been widely applied in the study of hydroxyl compounds in tannins and flavonoids, 26,27 extra-virgin olive oil, 28 biodiesel, 29 pyrolysis oil, 30−44 hydrothermal liquefaction (HTL) biocrude, 19 and upgraded bio-oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Schiff et al found in the experiment that the quantitative information of the product derived from hydroxyl-functional compound and a phosphorylating reagent can be determined through 31 P NMR, and corresponding chemical shift of phosphorus in the derivatization product is significantly different. 34 It has been reported that an unprecedented analytical method-quantitative 31 P NMR was used to quantitatively characterize all functional groups by labelling of all unstable hydroxyls with a phosphorus-containing reagent. 35 A study of the Li Mi's research team on the chemical shifts of phosphorylated products from 54 different compounds and TMDP in 31 P NMR can provides valuable and precise spectral information for characterizing lignocellulose-based compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years we have had substantial success in utilizing reagents such as 1 as 31 P NMR spectroscopic tags for speciating and quantitating total phenolic contents in mixtures. Here we report our progress in establishing the complementarity of RP HPLC and 31 P NMR spectroscopy in speciating and quantitating phenols in two coal liquefaction resids.
…”
Section: Introductionmentioning
confidence: 99%